Analysis Of Battery LiFePO4 Pack Capacity As An Alternative Energy Source In Water Pump Shimizu PS-135 E - Luwis H. Laisina; Arnold J. Kastanja; Nikodemus Lewier (International Journal of Multidisciplinary Sciences and Arts, 2024)
Electrical energy is a basic need for society and is a fairly economical resource that can be used for various activities. Human activities are supported by electrical energy. Electrical energy has important role in supporting all activities such as the industrial, commercial building, transportation and housing sectors. Water pump Shimizu PS-135 E is a type of water pump that is widely used in family activities, its function is to supply water from water sources (reservoirs, wells) for family needs such as bathing and washing. The pump relies continuously use of electrical energy, it means that, if this energy source runs out, the pump will not be able to operate automatically and ultimately. For this reason, in this research, the LiFePO4 type battery is used as an alternative energy source to overcome the above problems. The results of the analysis in this research show that to run the water pump for 1.5 hours a 42,000 mAh 12 Volt LiFePO4 battery is required which is arranged in a 4S - 7P manner and as a battery protector a 60 A Daly type BMS is used. Testing the load on the water pump until the battery cut time showed that the battery drain time was 1.3 hours, the battery condition was 20% with a voltage of 12.89 Volts. AC output voltage 230.4 Volts, current 1.145 A, power (P) = 195 Watts, Power Factor 0.72. The volume of water produced in 1.3 hours (78 minutes) is 2,182 liters.